Evasão no Ensino Superior: uma análise no curso de agronomia da Universidade Federal do Cariri - Ferreira, Anna Karyne Martins e Silva (2019)
The present study had as objective to analyze the factors that influenced the students in the decision to abandon the course of Agronomy of the Federal University of Cariri. As a theoretical basis for evasion, we use the concepts defined by the Special Committee on Studies on Evasion in Brazilian Public Universities, created by the Ministry of Education / Secretary of Higher Education (MEC / SESu, 1996), presented in the document Diplomation, Retention and graduate studies in public higher education institutions, besides the contributions of Polydoro (2000) and Veloso; Almeida (2002). The study was developed through an exploratory research with qualitative approach, with data collection through the application of a structured and closed questionnaire, composed of 64 questions, sent by the Google Forms platform, whose questions dealt with socioeconomic conditions, student/family and student/university relations. In interpreting and analyzing data, we adopt Bourdieu's concept of cultural capital, because we understands that he explains how relations built outside and within the educational environment intersect and affect the teaching and learning process, influencing cases of avoidance. Of the total of 163 students evaded in the period from 2013 to 2017, 47 participated in the research and represented a sample equivalent to 28.8%. The results pointed out that some factors prior to the student's admission to the university are associated with their academic life and indirectly influence the decision to leave the course, for example, the economic condition of the family and parents' schooling. However, the three factors that most influenced students to avoidance are: option for another course with 61.7%, option for another institution with 38.3% and financial condition with 31.9%. Based on these results, we propose the creation of a pedagogical sector with student-oriented attendance, aiming at reducing cases of dropout in the course